Adsorption of colour, TSS and COD from palm oil mill effluent (POME) using acid-washed coconut shell activated carbon: Kinetic and mechanism studies - Yong yin, Sia; Tan, I. A. W.; Mohammad Omar, Abdullah (EDP Sciences, 2016)
The disposal of palm oil mill effluent (POME) without proper treatment before being discharged into natural water sources has become undesirable because of high concentration of suspended solid (SS), oil and grease (O&G), chemical oxygen demand (COD) and biological oxygen demand (BOD). This study investigated the feasibility of removing colour, total suspended solid (TSS) and COD using acid-washed coconut shell based activated carbon (CSAC) through the evaluation of the adsorption uptake as well as the adsorption kinetics and mechanism. The percentage removal of colour, TSS and COD from POME onto CSAC were 61%, 39%, 66%, respectively achieved within 48 hours of contact time. The kinetic models studied were pseudo-first-order (PFO), pseudo-second-order (PSO), and Elovich models. The intra-particle diffusion (IPD) model was studied to interpret the adsorption diffusion mechanism. The adsorption of colour, TSS and COD onto CSAC were best interpreted by the PSO model, and well fitted by the Elovich model. The IPD and Boyd plots indicated that IPD and film diffusion controlled the adsorption of colour, TSS and COD onto the CSAC.